Microwave processing of oil palm wastes for bioenergy production and circular economy: Recent advancements, challenges, and future prospects. (February 2023) - Foong, Shin Ying; Chan, Yi Herng; Lock, Serene Sow Mun; Chin, Bridgid Lai Fui; Yiin, Chung Loong; Cheah, Kin Wai; Loy, Adrian Chun Minh; Yek, Peter Nai Yuh; Chong, William Woei Fong; Lam, Su Shiung
Graphical abstract: Highlights: Various microwave processing techniques of oil palm wastes are reviewed. Microwave processing has significantly reduced the processing time. Products from microwave processing are of superior qualities and characteristics. Microwave processing has lower environmental impacts due to lower emissions. Continuous operation mode is vital for microwave's application in commercial scale. Abstract: The valorization and conversion of biomass into various value-added products and bioenergy play an important role in the realization of sustainable circular bioeconomy and net zero carbon emission goals. To that end, microwave technology has been perceived as a promising solution to process and manage oil palm waste due to its unique and efficient heating mechanism. This review presents an in-depth analysis focusing on microwave-assisted torrefaction, gasification, pyrolysis and advanced pyrolysis of various oil palm wastes. In particular, the products from these thermochemical conversion processes are energy-dense biochar (that could be used as solid fuel, adsorbents for contaminants removal and bio-fertilizer), phenolic-rich bio-oil, and H2 -rich syngas. However, several challenges, including (1) the lack of detailed study on life cycle assessment and techno-economic analysis, (2) limited insights on the specific foreknowledge of microwave interaction with the oil palm wastes for continuous operation, and (3) effects of tunable parameters and catalyst's behavior/influence on the products' selectivity and overall process's efficiency, remain to be addressed in the context of large-scale biomass valorization via microwave technology.